Absence of TERT promoter mutations in colorectal precursor lesions and cancer - Cruvinel-Carloni, Adriana (2018)
Hotspot mutations (c.-124bp G > A and c.-146bp G > A) in the promoter region of the TERT gene have been recently described in several types of solid tumors, including glioma, bladder, thyroid, liver and skin neoplasms. However, knowledge with respect to colorectal precursor lesions and cancer is scarce. In the present study we aimed to determine the frequency of hotspot TERT promoter mutations in 145 Brazilian patients, including 103 subjects with precursor lesions and 42 with colorectal carcinomas, and we associated the presence of such mutations with the patients clinical-pathological features. The mutation analysis was conclusive in 123 cases, and none of the precursor and colorectal carcinoma cases showed TERT promoter mutations. We conclude that TERT mutations are not a driving factor in colorectal carcinogenesis.